Estratégias espectroanalíticas para análise química inorgânica de plantas medicinais - Virgilio, Alex (2014)
This thesis describes the development of analytical procedures based on direct solid analysis by high-resolution continuum source atomic absorption spectrometry in graphite furnace (SS-HR-CS GF AAS) and aqueous solutions by flame (HR-CS F AAS), tungsten coil atomic emission spectrometry (WC AES), standard dilution analysis for inductively coupled plasma optical emission spectrometry (SDA ICP OES) and inductively coupled plasma mass spectrometry with a tandem mass spectrometer (ICP-MS/MS) for inorganic chemical analysis of medicinal plants. In the first study, SS-HR-CS GF AAS was evaluated for the determination of Al, Cr, Ni and V. The development of an atomizer heating program with an additional air-assisted pyrolysis step and use of chemical modifier for Cr, makes feasible the use of calibration with aqueous standards for solid sample analysis. Limits of detection of 3, 18 and 7 ng g-1 were obtained for Cr, Ni and V, respectively. Aluminum was determined by HR-CS F AAS due to its high content in the samples, and presented a LOD of 10 μg L-1. For studies involving the determination of Al, Cr and V by WC AES, it was developed a new method for atomizer temperature monitoring, in order to perform more accurate and controllable heating programs. The use of conditioned coils, chemical modifiers for sensitivity enhancement and a pyrolysis step produced lower limits of detection (0.1 mg g-1 Al, 9 μg g-1 Cr and 13 μg g-1 V) and better precision. In another study, it was evaluated the development and application of a new calibration method called standard dilution analysis (SDA) for the determination of Al, Ca, Fe, Mg, Mn and Zn by ICP OES. SDA combines the benefits of matrix matching as in the standard additions method, and the correction of interferences similarly to internal standardization approach without any instrumental modifications. The procedure has high sample throughput and it is suitable for routine analysis. SDA was compared to different conventional calibration methods for CRMs analysis and recoveries in the 88 - 112 % range were obtained by the proposed method. Limits of detection of 2 (Al) ; 0.1 (Ca) ; 0.02 (Mg) ; 0.3 (Fe), 0.1 (Mn) and 0.1 μg g-1 (Zn) were obtained. In the last study, it was evaluated the performance of ICPMS/ MS for As, Cd, Cr, Ni, Pb and V determination in phytotherapic drugs. By using the MS/MS configuration, oxygen in octopole reaction system (ORS) and oxide detection for As and Cr, results with good accuracy and precision were obtained. In these cases, limits of detection of 10 (As); 0.2 (Cd); 8 (Cr), 8 (Ni), 3 (Pb) and 2 ng g-1 (V) were obtained.